2017
DOI: 10.1136/bjophthalmol-2017-310518
|View full text |Cite
|
Sign up to set email alerts
|

Anterior segment optical coherence tomography angle and vault analysis after toric and non-toric implantable collamer lens V4c implantation in patients with high myopia

Abstract: There is a significant reduction in the iridocorneal angle after ICL V4c implantation. Furthermore, there is a change under mesopic conditions in both the iridocorneal angle and vault during long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…If we focus now on predictability, we can consider these procedures to be successful, since 90.6% and 93.9% of the eyes were within the ±0.50 and ± 1.00 D range of postoperative refractive error, respectively. Both values were also comparable and sometimes better (versus Ganesh et al [7], García-de-la-Rosa et al [10], and Niu et al [11]) than those found in previous studies (see Table 3). Similarly, SE was also good, being below a quarter of diopter (−0.09 ± 0.47D).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…If we focus now on predictability, we can consider these procedures to be successful, since 90.6% and 93.9% of the eyes were within the ±0.50 and ± 1.00 D range of postoperative refractive error, respectively. Both values were also comparable and sometimes better (versus Ganesh et al [7], García-de-la-Rosa et al [10], and Niu et al [11]) than those found in previous studies (see Table 3). Similarly, SE was also good, being below a quarter of diopter (−0.09 ± 0.47D).…”
Section: Discussionsupporting
confidence: 74%
“…e search was limited to publications written in English. e date of the last electronic search was March 24, 2020. e literature search based on these criteria resulted in 8 relevant contributions being considered [5][6][7][8][9][10][11][12]. Table 2 summarizes the information about the sample size (number of eyes), patients' age, and SE values of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, there was a negative correlation between the C-ICL and the ΔECD. Several reports [22][23][24][25][26] regarding the anterior chamber lens showed a decreased distance between the corneal endothelium and central ICL, which increased the loss of ECD. Two reports in 2017 emphasised the importance of C-ICL in reducing the loss of ECD.…”
Section: Discussionmentioning
confidence: 97%
“…This includes evaluation of pterygium [102], management guidance in ocular surface neoplasia [103], characterization of abnormalities associated with keratoconus [104-108], and evaluation of corneal wound healing [109-113]. The role of AS-OCT is also important in preoperative, intraoperative, and postoperative assessment of patients requiring corneal surgeries [111, 114-118]. Recently, application of intraoperative AS-OCT has been proven to be helpful in deep anterior lamellar keratoplasty [119-121], femtosecond cataract surgery [122], as well as during Descemet stripping automated endothelial keratoplasty (DSAEK) [123] and Descemet membrane endothelial keratoplasty (DMEK) [124, 125].…”
Section: Imaging and Ne(ur)ovascularizationmentioning
confidence: 99%